DECREASEMENT OF COLOUR AND COD CONTENT OF THE LIQUID WASTE PRODUCT FROM THE JEANS WASHING INDUSTRY BY CHITOSAN AND Trametes versicolor - Rumondang Bulan; Mersi Suryani Sinaga; Darnianti Darnianti (Universitas Gadjah Mada, 2010)
Chitosan and Trametes versicolor were used as the material for processing liquid waste product from the jeans washing industry in this study as they were more economics and no negative damage in the environmental life. This research is to find out the chitosan and Trametes versicolor effect as the coagulant in decreasing the colour and the COD content of the liquid waste product from the jeans washing industry using the coagulation method and floculation. The dosage of chitosan and Trametes versicolor were 200, 400, 600, 800 and 1000 mg/L of the liquid waste product whereas the combination of chitosan and Trametes versicolor were 4:1, 3:2, 2:3 and 1:4. The data resulted from the analysis were shown as a graphics. The research results show that the optimum dosage of chitosan as coagulant was 800 mg/L which was able to decrease the colour intensity. For blue colour, the intensity decreased from 1.2 to 0.1%; the yellow colour intensity decreased from 0.9 to 0.0% and the COD 91.23%. The optimum dosage of Trametes versicolor of 600 mg/L was able to decrease the blue colour intensity from 1.2 to 0.11%; the yellow colour intensity from 0.9 to 0.1% and the COD was 91.37%. By using the combinationof chitosan and Trametes versicolor it was shown that the best result was using the 3:2 ratio which was able to decrease the blue colour intensity from 0.9 to 0.1% and the yellow colour intensity from 0.9 to 0.0% and the COD was 86.68%.